The Influence Of Self Regulation On Creative Self Efficacy Among Students In Inclusive Gifted Schools In Saudi Arabia: The Mediating Role Of Students’ Creative Thinking Skills - Salem M, Aljumyd, Meshal (2021)
Educators not only shape the minds of students but also co-construct their minds, build their skills and perceptions towards their abilities and ultimately enhance their performance. Such a co-construction process can be achieved by developing students’ self-efficacy and self-regulations in which is mediated by their creative thinking skills and moderated by their giftedness. The creative thinking skills of students can significantly predict their self-efficacy when they are considered ‘gifted’. In the Kingdom of Saudi Arabia (KSA), interest in gifted students began to grow in 1998 as can be seen in the introduction of programmes geared towards identifying gifted students and developing both their creative thinking skills and self-efficacy. The counselling and gifted education literatures have devoted limited attention to those mechanisms that underlie the difficulties faced by creative students in KSA. This study examines the relationship between KSA students’ self-regulation and self-efficacy through the mediation of creative thinking skills and giftedness. This study also proposed a framework relates these students’ self-regulation with their creative self-efficacy through the intervention of their creative thinking skills. This study used a simple random sampling technique that give each element in the underlying population the equal probability to be selected.